CRITERIA FOR MEASURING INFLUENCE OF THE SOCIAL MEDIA MARKETING STRATEGY FOR AGILITY STARTUP - Putra, Azka Razaqa; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT This paper aims to give an outlook regarding what types of criteria the company Agility Startup should focus on in order to improve their social media marketing strategy. The research was conducted to give a compact outlook on what types of Key Performance Indicators should be looked at in order to give a picture regarding the firm’s performance on their social media marketing efforts. To complete the research, the author has utilized desk research by using various sources such as journals from Saxion Library, Google Scholar, and Elsevier. The results show that Agility Startup should be focusing on different types of factors for each social media platform that they use, with some overlap between each program on the KPIs. The company should also look at other varying factors in the users of social media marketing.